Sistematična preureditev mestnih ulic - Fallast, M. (Urbani izziv, 2021)
The reintroduction of green infrastructure is a recognized approach to mitigating heat islands and flash floods in urban areas. Depending on its type and extent, green infrastructure (GI) can reduce local urban temperatures significantly and at the same time reduce the risk of flooding. This article views the streetscape as an important area of activity for GI-based climate-adaptation interventions for two main reasons: it serves as a conduit for urban human activity and mobility, and it acts as a significant heat store. The approach proposed unites some key elements that can form the basis for all future public-realm (streetscape) design, promoting a truly climate-responsive urban environment. These include reduction of sealing to only essential areas, decentralized water management using rain-garden technology, low maintenance, aesthetic planting supporting biodiversity, and sensor-based monitoring of thermal comfort parameters to optimize measures. It utilizes low-cost sensors for obtaining thermal comfort data to locate urban heat islands. It also proposes a GIS-based decision tool bringing together relevant data sets: temperature, level of surface sealing, and flood risk, as well as aspects such as the location of services, traffic, and urban planning. A pilot application as part of an ongoing Austrian government-funded climate adaptation project is described in which this methodology has been applied.
Keywords: cities; climate change; gospodarjenje s padavinsko vodo; javni prostor; mesta; padavinske vode; podnebne spremembe; public space; sensor technology and digitization; senzorska tehnologija in digitalizacija; stormwater management,; street drainage; ulično odvodnjavanje